2017
DOI: 10.1002/adsc.201601265
|View full text |Cite
|
Sign up to set email alerts
|

Vinylogous Nucleophilic Substitution of the Hydroxy Group in Diarylmethanols with 3‐Propenyl‐2‐silyloxyindoles: Towards the Synthesis of α‐Alkylidene‐δ‐diaryl‐2‐oxindoles

Abstract: We report herein a highly stereoselective method for the indium triflate‐catalyzed vinylogous substitution of the hydroxy group of diarylmethyl alcohols with 3‐alkenyl‐2‐silyloxyindoles, which affords broadly substituted α‐alkylidene‐δ‐diaryl‐2‐oxindole products with high efficiency and complete γ‐site and Z‐selectivity. The reaction displays very wide substrate scopes for both the reactants, benzhydryl alcohols and 3‐alkenyl‐2‐silyloxyindoles. The utility of the substituted adducts is shown by their conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The synthesis of α-alkylidene-δ-diaryl-2-oxindoles 975 was accomplished by Singh et al through metal-catalyzed vinylogous nucleophilic substitutions of diarylmethanols 974 with alkylidene silyloxyindoles 973 ( Scheme 249 ). 643 …”
Section: Vinylogous Amides and Lactamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of α-alkylidene-δ-diaryl-2-oxindoles 975 was accomplished by Singh et al through metal-catalyzed vinylogous nucleophilic substitutions of diarylmethanols 974 with alkylidene silyloxyindoles 973 ( Scheme 249 ). 643 …”
Section: Vinylogous Amides and Lactamsmentioning
confidence: 99%
“…639 The products 967 were prepared in good chemical yields, albeit with moderate enantioselectivities. 643 The reactions were catalyzed by indium triflate and proceeded efficiently giving the Z-configured γ-alkylated compounds 975, exclusively. The authors explained the observed Z-selectivity by the vinylogous attack of the s-cis conformer of silyloxyindoles on the diarylmethane cation intermediates, while steric concerns were invoked to account for the remarkable γ-selectivity.…”
Section: Other Reactionsmentioning
confidence: 99%
“…Although α-alkylidene-δ-diaryloxindoles were obtained with complete γ-site and Z-selectivity, the reaction was not attempted with chiral indium complexes. 33…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…1b ). 4 Organofluorine compounds are important molecules employed in agro- and medicinal chemistry 5 and chiral compounds containing the trifluoromethyl group (CF 3 ) bonded to a stereogenic centre are active against various diseases. In particular, tertiary trifluoromethyl alcohols are important building blocks for the synthesis of biologically active compounds and drugs ( Fig.…”
Section: Introductionmentioning
confidence: 99%